INFLUENCE OF SOCIAL MEDIA ON DEMOCRACY: Twitter as a Tool of Social Uprising During #OccupyGezi - Peixoto, Özgür de Jesus (2017)
Dissertação de Mestrado em Democracia e Governação - Roads to Democracy(ies) apresentada à Faculdade de Economia